Optimal Control Problem for a Conveyor-Type Production Line - Pihnastyi, O. M.; Khodusov, V. D. (Springer Science+Business Media, 2018)
A method for constructing optimal control of the conveyor-type flow line parameters is developed. The model of the conveyor line is represented by the partial differential equation, which allows to take into account the distribution of products along the technological route as a function of time. Various variants of stepped speed control of the conveyor belt are investigated. The features of step control are determined. The divergence the rate of output by the flow line from the given demand for different parameters of step control is shown.
Keywords: conveyor; subject of a labour; production line; PDE-model of the production; technological position; transition period; production management systems